2014
DOI: 10.1007/s40593-014-0023-y
|View full text |Cite|
|
Sign up to set email alerts
|

A Multimedia Adaptive Tutoring System for Mathematics that Addresses Cognition, Metacognition and Affect

Abstract: This article describes research results based on multiple years of experimentation and real-world experience with an adaptive tutoring system named Wayang Outpost. The system represents a novel adaptive learning technology that has shown successful outcomes with thousands of students, and provided teachers with valuable information about students' mathematics performance. We define progress in three areas: improved student cognition, engagement, and affect, and we attribute this improvement to specific compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
113
0
12

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(126 citation statements)
references
References 63 publications
1
113
0
12
Order By: Relevance
“…MathSpring is a math practice environment inside an adaptive tutor that provides math instruction embedded within extensive hints, help, and links to external instructional videos (Arroyo et al 2014). The system is an integration of Wayang Outpost and ASSISTments.…”
Section: Funded Projectsmentioning
confidence: 99%
“…MathSpring is a math practice environment inside an adaptive tutor that provides math instruction embedded within extensive hints, help, and links to external instructional videos (Arroyo et al 2014). The system is an integration of Wayang Outpost and ASSISTments.…”
Section: Funded Projectsmentioning
confidence: 99%
“…Presently, their work has focussed on deducing learner characteristics (in the SIgBLE prototype), which teachers can use when deciding on feedback. Arroyo et al (2014) describes a system that identified and targeted affective states, additionally using measures of progress and motivation to improve student cognition, engagement and affect.…”
Section: Adaptation Of Learning Systems To Motivation and Affective Smentioning
confidence: 99%
“…Developing strategies to reduce stress and regulate emotions allows students to optimize performance in many cognitive tasks (Arroyo et al, 2014). For example, students who have a positive self-concept of their mathematics ability perform better in math classes, possibly because they do not attribute poor math performance as a SET, but rather interpret failure as information and as an opportunity for learning and growth.…”
Section: Introductionmentioning
confidence: 99%